A ratcheting mechanism-based numerical model to predict damage initiation in twin-disc tests of premium rail steels. (April 2023) - Li, Yifei; Wu, Yiping; Mutton, Peter; Qiu, Cong; Yan, Wenyi
Highlights: A ratcheting mechanism-based numerical model was applied to predict damage initiation in twin-disc tests of premium rail steels. Wear- and RCF-dominated damages are distinguished by the depth of the ratcheting mechanism-based damage initiation locations. A higher creepage results in a shallower damage initiation location and a shorter damage initiation life. The initial wear rate increases with a higher creepage for wear-dominated damage. HE2 rail steel presents the longest damage initiation life and the lowest initial wear rate compared to HE1 and LAHT. Abstract: This work presents a ratcheting mechanism-based numerical model to study the initiation location and initiation life of rolling contact fatigue (RCF) or wear damage and the initial wear rate of premium rail steels under the laboratory twin-disc test conditions. Twin-disc tests are widely used in the studies of rail steels due to their ability to reproduce critical aspects of full-scale wheel-on-rail contact under controlled conditions and a relatively short test period compared to field tests. This study introduces a computational model to simulate the cyclic rolling contact for three premium rail steels (HE1, HE2, and LAHT) against wheel steel AAR Class-C under twin-disc test conditions. The cyclic rolling contact is achieved by repeatedly moving a non-Hertzian distribution of contact pressure and the calculated longitudinal surface traction upon a segment of the circumferential surface of the lower disc until a stabilized maximum ratcheting strain rate is reached. The RCF or wear damage initiation location is determined by the location showing the stabilized maximum ratcheting strain rate, and the damage initiation life is estimated by applying the ratcheting failure mechanism. Wear and RCF damages are distinguished by the depth of the damage initiation location. Wear damage is dominant when the location is near the surface. Otherwise, the damage will be RCF-dominated. The initial wear rate due to wear-dominated damage is estimated by identifying a critical profile and affected volume of worn material within the ratcheting strain rate field. The predicted initial wear rate is compared with the experimental result of the examined contact pair. This research can assist in a more profound understanding of the experiment results of a twin-disc test and provide a numerical basis for an experimental twin-disc test design. Furthermore, it may provide significant references for choosing rail steels.